INFORMATION TERRORISM AS A THREAT TO THE NATIONAL SECURITY OF UKRAINE - Leonov, Borys; Lykhova, Sofia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: to investigate the types and forms of information terrorism in the context of the threat to Ukraine’s national security. The methodological basis of the study consists of comparative law and system analysis, formal law method, method of interpretation, hermeneutic and methods of analysis and synthesis. Discussion: the problem of combating information terrorism requires an analysis of various crisis phenomena and the structure of terrorism itself as a phenomenon that has come a long way from lone suicide bombers to huge terrorist organizations that carry out terrorist attacks, to the use of information for intimidation of a significant number of people. Results: one of the main threats to information security is information terrorism as a form of destructive influence aimed at manipulating or intimidating the population or causing harm to society, the state or individuals through information technology in order to force public authorities, international organizations, legal entities or individuals (group of persons) to take an action (or refrain from doing so). It is indisputable that today the Internet has complicated the protection of information resources. Terrorist groups and individual terrorists around the world enjoy its features and benefits, trying to influence both domestic and foreign policies of states, using a variety of information technologies to achieve their criminal goal. The legal literature indicates that the availability of information technology significantly increases the risks of information terrorism, and the development of information infrastructure of society contributes to the creation of additional risks of information terrorism, which in today’s globalization and internationalization becomes extremely destructive.